1996
DOI: 10.1161/01.cir.94.12.3355
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Transplant Coronary Arteriosclerosis in Rabbits by Chronic Estradiol Treatment Is Associated With Abolition of MHC Class II Antigen Expression

Abstract: Estradiol treatment of cardiac allograft recipients abolishes MHC class II antigen expression in the coronary arteries and decreases macrophage infiltration in all three layers of the vessel wall, whereas T-lymphocyte infiltration is decreased only in the myointima. These findings are associated with estradiol inhibition of myointimal proliferation. Thus, estradiol treatment may have a beneficial effect on graft arteriosclerosis through immune mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 29 publications
2
30
0
3
Order By: Relevance
“…Similarly, both E 2 and synthetic ER agonists normalized NF-kB activation and pro-inflammatory cytokine production as well as reduced TLR4 expression in Kupfer cells following trauma-hemorrhage in rats and mice, and these effects were shown to be specifically mediated by ERa (Hsieh et al 2007, Suzuki et al 2007. In addition, transplant arteriosclerosis in rats or rabbits as well as macrophage infiltration into the allograft intima were potently reduced in E 2 -treated recipients, and this was associated with almost complete suppression of MHC-II antigen expression in transplanted arteries (Lou et al 1996, Saito et al 1998. Most recently, ERa-deficient macrophages were found refractory to IL4-induced activation of anti-inflammatory phenotype in vitro and presented with elevated expression of chemokines and markers of immune cell activity, when isolated from animals with myeloid-specific ERa deficiency (Ribas et al 2011).…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 89%
“…Similarly, both E 2 and synthetic ER agonists normalized NF-kB activation and pro-inflammatory cytokine production as well as reduced TLR4 expression in Kupfer cells following trauma-hemorrhage in rats and mice, and these effects were shown to be specifically mediated by ERa (Hsieh et al 2007, Suzuki et al 2007. In addition, transplant arteriosclerosis in rats or rabbits as well as macrophage infiltration into the allograft intima were potently reduced in E 2 -treated recipients, and this was associated with almost complete suppression of MHC-II antigen expression in transplanted arteries (Lou et al 1996, Saito et al 1998. Most recently, ERa-deficient macrophages were found refractory to IL4-induced activation of anti-inflammatory phenotype in vitro and presented with elevated expression of chemokines and markers of immune cell activity, when isolated from animals with myeloid-specific ERa deficiency (Ribas et al 2011).…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 89%
“…Furthermore, Foegh et al demonstrated that estrogens ameliorate transplant arteriosclerosis in cardiac and aortic allografts [6,18,191. The role of estrogens, however, in the development of renal disease is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The current study does not answer this question, as we did not observe the expression of PDGF-B and other growth factors that are thought to be involved in the development of GCA. 30 Further studies on these issues are needed to clarify possible mechanisms underlying the effects of PDGF-A and other growth factors on cardiac grafts.…”
Section: Discussionmentioning
confidence: 99%